Artemidora’s shield. Gender and formation in “Amor di Marfisa” by Danese Cataneo (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2022)
Focusing on the epic-chivalric poem Amor di Marfisa (1562) by Danese Cataneo, this article aims to investigate how the later epic tradition rewrites and reshapes the model of Ariosto concerning gender issues and the education of the heroine. Cataneo selects from Ariosto those narrative structures and literary themes useful for the definition of a canon of “virtù donnesca”, and reshapes them with classical myths, such as the myth of Lucretia. Marfisa and the newly invented character of Artemidora – the queen of Iceland, very similar to the original Bradamante – are two heroines-in-training: once they have completed their journey, they are destined to reach the highest degrees of feminine virtue, the virgin-queen and the married-queen.
Keywords: Ariosto; Marfisa; Renaissance Epic; Gender Studies; virtù donnesca; Lucretia